Keterlibatan dan Kepentingan Amerika Serikat dalam Konflik Rusia-Ukraina Tahun 2015-2021 - Salsabila, Nela Avrilia; Ribawati, Eko (Peneliti.net, 2024)
After the collapse of the Soviet Union, the United States became the sole superpower, giving it the confidence to intervene in the internal affairs of other countries. This kind of phenomenon is visible today in the Russian-Ukrainian conflict. In this conflict the United States was involved by providing support to Ukraine in facing Russia. The involvement of the United States is seen as their effort to guarantee national security and the interests of their country. This article aims to explain how the United States was involved in the conflict between Russia and Ukraine, as well as how the United States' national interests behind its involvement in the conflict colored the dynamics of relations between Russia and Ukraine from 2015 to 2021. The research methodology uses a descriptive method with a qualitative approach. The data collection technique was carried out using the literature study method using secondary data relevant to the research topic. The problems in the conflict between Russia and Ukraine, and the involvement of the United States in providing assistance and support to Ukraine can be seen as a reflection of the competitive conflict between the United States and Russia. The United States' efforts to maintain its position as hegemon in politics and international relations are the reason for the United States' goal of preventing Russian influence in Ukraine.